Jogos propostos por autores de livros didáticos : uma caracterização de uso (s) por professores de matemática dos anos finais do ensino fundamental (Aracaju/SE) - Santos, Claudiene dos (2019)
This text presents the result of a research that aimed to characterize if / how teachers of the final years of elementary school use the mathematical games that are proposed by authors of PNLD / 2017 textbooks adopted for state schools of public schools. in Aracaju / SE. Initially, the three most used PNLD / 2017 collections in Aracaju / SE were examined, namely: Understanding Mathematics and Practice, Willingness to Know Mathematics and Bianchini Mathematics. From this choice, for each collection, an educational institution was selected in each geographical area of the city to apply questionnaires to mathematics teachers with the intention of achieving the proposed objective. The data collection instruments consisted of a questionnaire containing twenty-four questions, ranging from the personal training of each research participant to whether / how this resource was applicable in the classroom and an interview with questions aimed at identifying the use made of games by teachers. For an understanding of mathematical game Grando (1995, 2000) was used. By examining the questionnaires, it was possible to characterize that eight of the twelve respondents are aware of the presence of mathematical games in the textbook, but only five use the games indicated by the authors of the books they adopt. Such use is made by teachers to work, mainly, the contents of fractions, percentages, angles, potentiation, equations, functions and natural numbers. In the interview, it can also be seen that the games are made by the survey respondents or their students and that, in all cases, are adapted by the teachers at the class level. Part of the participants also claimed to use other didactic resources, even games indicated by authors of other collections. It was also identified that the five research participants who use the games proposed in the book do so to: evaluate the student, introduce and develop the contents, promote socialization, assist in problem solving and fix the contents. Some of these uses happen in isolation and others at the same time.